Effects of periodic trench structure on cathodo‐luminescence in InGaN/GaN multi‐quantum wells. Issue 14 (1st July 2014) - Kim, G.; Kim, S.W.; Kim, J.H.; Park, E.; Park, B.‐G.
Abstract : To reduce strain and the quantum‐confined Stark effect (QCSE), periodic trenches in an InGaN/GaN multi‐quantum well (MQW) are patterned by electron‐beam (e‐beam) lithography and the inductively‐coupled plasma (ICP) dry etching process. The effects of the fabricated structure are investigated by measuring cathodo‐luminescence (CL) spectra and comparing it with the data of an as‐grown sample without trench patterns. The peak wavelength of the prepared samples is clearly blue‐shifted, and it is confirmed that the strain and the QCSE are reduced by the effects of the trench structures. It is also confirm that the peak intensity of CL spectra shows a maximum when 90% of the active region is remaining, because the trench patterns reduce the light emitting area as well as the strain and the QCSE.